2021
DOI: 10.52165/sgj.13.3.311-321
|View full text |Cite
|
Sign up to set email alerts
|

Body and Performance in Rhythmic Gymnastics: Science or Belief?

Abstract: This study aims to identify whether competitive rhythmic gymnasts feel body dissatisfaction and, if so, to analyze the factors related to its development and the implications for the gymnasts’ health. We interviewed 28 female gymnasts, aged between 13 and 16 years, from three teams in one Brazilian state. Based on the thematic analysis, we present the following themes: “Body, Performance, and Misconceptions in Rhytmic Gymnastics (RG)” and “Body weight in RG: Belief vs. Science.” Gymnasts’ dissatisfaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The participating parents were concerned about their children’s special diets and the expectations set by their sport; the coaches simultaneously expressed their expectation for and concern about keeping a lean shape; while the athletes felt unable to meet the sport-specific expectations or to exert adequate control over their weight. In line with previous findings, all three groups associated sport success with a lean shape ( Kaur and Koley, 2019 ; de Oliveira et al, 2021 ). The general belief that no athlete is good enough without a lean shape potentially affects athletes’ satisfaction with and confidence in their performance has also been highlighted in previous studies ( Sundgot-Borgen and Torstveit, 2004 ; Kong and Harris, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…The participating parents were concerned about their children’s special diets and the expectations set by their sport; the coaches simultaneously expressed their expectation for and concern about keeping a lean shape; while the athletes felt unable to meet the sport-specific expectations or to exert adequate control over their weight. In line with previous findings, all three groups associated sport success with a lean shape ( Kaur and Koley, 2019 ; de Oliveira et al, 2021 ). The general belief that no athlete is good enough without a lean shape potentially affects athletes’ satisfaction with and confidence in their performance has also been highlighted in previous studies ( Sundgot-Borgen and Torstveit, 2004 ; Kong and Harris, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…In sports disciplines requiring specific body mass and emphasizing physical image (e.g., gymnasts, combat sports athletes, middle- and long-distance runners, road cyclists, etc. ), the pressure for weight loss during tapering for competition could be a precipitating factor for the manifestation of inadequate and sometimes extreme dietary behaviors [ 288 , 289 ]. This pursuit of the ideal body is deeply linked to the propensity for sports to cause EDs, particularly bulimia nervosa, as athletes are not guided towards a healthy diet but rather urged to achieve a standardized, “model body” [ 289 ].…”
Section: Eating Disorders and Relative Energy Deficiency In Sport (Reds)mentioning
confidence: 99%
“…A study by Stirling et al (2012) encompassing eight elite rhythmic athletes who retired from the sport found that all these athletes cited changes in body composition as one of the most distressing aspects of the retirement transition. The fact is that body dissatisfaction and demands for a body ideal are present in RG, and can directly and negatively affect athletes (De Oliveira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%